Penerapan Demokrasi Kepemimpinan Dalam Organisasi Kecil Berlandaskan Pancasila - Maryanti, Natasya Susy; Rumintan , Susen Dorma; Riris, Sari Octavia; Pramija, Ying; Yunita, Sri (Jurnal Pendidikan Indonesia, 2022)
Democracy is a form of government in which all citizens have equal rights to make decisions that can change their lives. The word democracy comes from the term demokratia which means “rule of the people”, is a combination of two words, demos means people (people) and kratos. Means power or government. The purpose of this study, among others, is that researchers explore the events or objects under study, such as seeing how a leader leads. And in order to obtain information about the democratic leadership system of Pancasila and the 1945 Constitution, it is still being applied. This study uses a qualitative descriptive method as a translation method. This method will describe the data that the authors have collected through interviews, namely by holding direct questions and answers with the two leaders or one of the heads of campus organizations regarding the implementation of leadership democracy in organizations based on Pancasila.